2022
DOI: 10.1021/acsinfecdis.2c00253
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of Semisynthetic Glycopeptide Antibiotics: 2014–2022

Abstract: The accelerated appearance of drug-resistant bacteria poses an ever-growing threat to modern medicine’s capacity to fight infectious diseases. Gram-positive species such as methicillin-resistant Staphylococcus aureus (MRSA) and Streptococcus pneumoniae continue to contribute significantly to the global burden of antimicrobial resistance. For decades, the treatment of serious Gram-positive infections relied upon the glycopeptide family of antibiotics, typified by va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 220 publications
0
29
0
Order By: Relevance
“…Notable examples are the vancomycin analogues with guanidium modifications reported by Wu et al that showed enhanced activity against resistant strains of S. aureus . Additionally, an overview of the recent advances regarding a wide range of vancomycin analogues can be found in the review article by van Groesen et al for further information on this subject.…”
Section: Other Promising Approaches For the Treatment And Diagnosis O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notable examples are the vancomycin analogues with guanidium modifications reported by Wu et al that showed enhanced activity against resistant strains of S. aureus . Additionally, an overview of the recent advances regarding a wide range of vancomycin analogues can be found in the review article by van Groesen et al for further information on this subject.…”
Section: Other Promising Approaches For the Treatment And Diagnosis O...mentioning
confidence: 99%
“…Notable examples are the vancomycin analogues with guanidium modifications reported by Wu et al 197 that showed enhanced activity against resistant strains of S. aureus. Additionally, an overview of the recent advances regarding a wide range of vancomycin analogues can be found in the review article by van Groesen et al 198 for further information on this subject. Compounds 88−90 (Figure 45) are part of a series of porphyrin conjugates with lysins which showed potential as photodynamic antimicrobials that are active after irradiation.…”
Section: Antibacterial Conjugates Activated By β-Lactamases or Trigge...mentioning
confidence: 99%
“…They disrupted the bacterial membrane integrity and lead to cell death finally by binding to the lipid A moiety of lipopolysaccharides (Wang et al., 2022). In the 1950s, vancomycin, a cyclic glycopeptide antibiotic isolated from microbial fermentation of Borneo soil, was found to have an inhibitory effect on penicillin‐resistant strains (van Groesen et al., 2022). The antimicrobial mechanism of vancomycin is the combination of its N‐terminal and D‐Ala‐D‐Ala residues in the C‐terminal of a peptidoglycan precursor (van Groesen et al., 2022).…”
Section: Function and Bioactive Mechanism Of Mdcpsmentioning
confidence: 99%
“…In the 1950s, vancomycin, a cyclic glycopeptide antibiotic isolated from microbial fermentation of Borneo soil, was found to have an inhibitory effect on penicillin‐resistant strains (van Groesen et al., 2022). The antimicrobial mechanism of vancomycin is the combination of its N‐terminal and D‐Ala‐D‐Ala residues in the C‐terminal of a peptidoglycan precursor (van Groesen et al., 2022). Because the peptidoglycan precursor locates at the outer surface of the bacterial cell plasma membrane, their binding precludes its transpeptidation reaction and inhibits the synthesis of the bacterial cell walls (Figure 3a).…”
Section: Function and Bioactive Mechanism Of Mdcpsmentioning
confidence: 99%
“…In addition, a survey conducted by three major pharmaceutical companies in 2006 revealed that two-thirds of drug candidates contain an amide group . Furthermore, medium-sized amide molecules like peptides and glycopeptides have recently attracted considerable attention as important targets in the discovery of novel drugs . In light of this growing demand for amide molecules, the ACS Green Chemistry Institute Pharmaceutical Roundtable included the goal to develop “general methods for catalytic/sustainable (direct) amide or peptide formation” as one of the 10 key green chemistry research areas in 2018 …”
mentioning
confidence: 99%